STRATEGI GURU PAI DALAM MENINGKATKAN KESADARAN SOSIAL MELALUI PELAJARAN FIKIH PADA SISWA SMPN 1 PASAK TALAWANG` - Santiani, Santiani; Azizah Nur Kumala (Cahaya Ilmu Bangsa Institute, 2024)
Social awareness is an important aspect in the formation of student character to create a generation that is caring and responsible towards the social environment. This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in increasing students' social awareness through Fiqh learning at SMPN 1 Pasak Talawang using qualitative descriptive methods and a case study approach. The results of the study show that PAI teachers apply various strategies, such as contextual approaches, integration of social values into learning, and practice-based methods, such as simulations and group discussions, as well as involving students in social activities, such as community service and visits to orphanages. These strategies successfully increased students' social awareness, reflected in their more caring, empathetic, and responsible behavior. This study contributes to the development of a Fiqh learning model that is not only focused on mastering the material but also on the formation of students' social character, making it relevant for teachers and education policymakers in creating effective and meaningful learning.